THE INFLUENCE OF STORE ATMOSPHERE ON CONSUMERS’ INTEREST TO BUY CASE STUDY AT LOTTE WHOLESALE LAMPUNG IN POST PANDEMI COVID-19: PENGARUH STORE ATMOSPHERE TERHADAP MINAT BELI KONSUMEN STUDY KASUS DI LOTTE GROSIR LAMPUNG PADA MASA PASCA PANDEMI COVID-19 THE - najah, khoirun; A . Efendi, A . Efendi; Subagja, Ghia (Jurnal Kompetitif Bisnis, 2023)
This study aims to determine the effect of store atmosphere on buying interest at Lotte Grosir Lampung during the post-covid-19 pandemic. The sampling technique in this study was non-probability sampling with accidental sampling technique with a sample of 110 respondents. The data collection technique was obtained through distributing questionnaires which were distributed via Google forms to social media via direct messages, through field observations conducted from 16 September to 25 October 2021 and also obtained through documentation. Data analysis in this study used descriptive analysis and simple linear regression analysis. Based on the results of research and data analysis, it shows that store atmosphere has a positive and significant effect on purchase intention with an R square value of 0.685 or 68.5%.